Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1136/bjsports-2012-091707
|View full text |Cite
|
Sign up to set email alerts
|

The time course of in vivo recovery of transverse strain in high-stress tendons following exercise

Abstract: Despite structural and biochemical differences between the Achilles and patellar tendon, the mechanisms underlying transverse creep recovery in vivo appear similar and are highly time dependent. These novel findings have important implications concerning the time required for the mechanical recovery of high-stress tendons following an acute bout of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“… 22 Studies of the acute response of normal tendons to exercise have described a multitude of physiological processes including changes in vascularity, 23 genetic expression 24 and mechanical properties. 25 Our results extend those of a number of studies of lower limb tendons, where pathological tendons exhibit an altered loading response compared with healthy tendon. People with Achilles tendinopathy have been found to have an altered response to loading, either in the form of a smaller initial reduction in tendon thickness (5% reduction vs 21% reduction in thickness in controls) and a slower return to normal tendon dimensions in response to eccentric exercise 5 or as an increase in tendon thickness after concentric and eccentric exercise.…”
Section: Discussionsupporting
confidence: 88%
“… 22 Studies of the acute response of normal tendons to exercise have described a multitude of physiological processes including changes in vascularity, 23 genetic expression 24 and mechanical properties. 25 Our results extend those of a number of studies of lower limb tendons, where pathological tendons exhibit an altered loading response compared with healthy tendon. People with Achilles tendinopathy have been found to have an altered response to loading, either in the form of a smaller initial reduction in tendon thickness (5% reduction vs 21% reduction in thickness in controls) and a slower return to normal tendon dimensions in response to eccentric exercise 5 or as an increase in tendon thickness after concentric and eccentric exercise.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, rope skipping represents in this context a more monotonous ankle‐straining activity. The examined healthy individuals did not show any signs of intratendinous edema or hyperemia, but these results are, at least in part, controversially discussed in literature as well . Both the reduction of tendon volume and increase in OSR after exercise might indicate a loss of free water within the tendon.…”
Section: Discussionmentioning
confidence: 80%
“…Most scans were performed after the first match of the day. Although previous studies have shown an immediate decrease in anterior‐posterior tendon diameter immediately post‐exercise (Wearing et al., ), mechanical loading seems to take some time to exert effect on the structure of the tendon detected by UTC. A review on the response of a tendon to loading proposed that the metabolic response peaks only 24 h after mechanical loading (Magnusson et al., ) In addition, no changes in echo types were found 1 day after an Australian football game, while there was a change in structure 2 days after a game (Rosengarten et al., ).…”
Section: Discussionmentioning
confidence: 81%